Limited home state measures in the WTO Investment Facilitation for Development Agreement: A missed opportunity or a starting point? - Rodrigo Polanco Lazo (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
This Perspective explores how the Investment Facilitation for Development Agreement (IFDA), recently made public at the World Trade Organization's 13th ministerial conference, could be used as a starting point to include additional home state measures to facilitate outward investment in other international investment agreements or national regulations.
Keywords: 330